Fabrication of Maize-Based Nanoparticles at Home: A Research-Based Learning Activity - Mario Moisés Alvarez; Lilia del Carmen Flores-Cruz; Sara Cristina Pedroza-González; Grissel Trujillo-de Santiago (MDPI AG, 2022)
Nanotechnology is an interdisciplinary field that promises to reshape many spheres of our lives. One core activity in nanotechnology is the synthesis of nanoparticles. Here, we introduce a research-based activity centered on the use of zein, the main constitutive protein in maize, as a raw material for the synthesis of nanoparticles. In the context of the contingency imposed by COVID-19, this experimental activity was designed to be independent of a central laboratory. Therefore, it was enabled by a portable heating do-it-yourself (DIY) device that the students assembled in their own home. We describe the implementation of this activity as part of a graduate-level seminar series, and share our observations. We assessed the students' knowledge on seven topics related to nanotechnology, do-it-yourself devices, and protein synthesis. The students appeared to perceive that their degree of knowledge had advanced (on average) in all the learning topics; the students stated that their degree of knowledge in the topics of assembly of devices and protein structure had advanced the most. The results of this assessment suggest that this simple, hands-on, research-based activity effectively engaged students in a learning process that allowed them to integrate knowledge while exercising their experimental skills. In addition, we show that these types of activities are suitable for implementation even in circumstances of restricted access to laboratory facilities, such as the ones recently experienced during the pandemic.